An annotated catalogue of the pygmy grasshoppers of the tribe Scelimenini Bolívar, 1887 (Orthoptera: Tetrigidae) with two new Scelimena species from the Malay Peninsula and Sumatra - Muhammad, Amira Aqilah; Tan, Ming Kai; Abdullah, Nurul Ashikin; Azirun, Mohammad Sofian; Bhaskar, Dhaneesh; Skejo, Josip (Zootaxa, 2018)
Pygmy grasshoppers (Tetrigidae) are a speciose group of complicated taxonomy, with many species requiring clarification on their species boundaries, and more still awaiting discovery. Two new species of Scelimena Serville, 1838 are described: (1) from S. discalis species group S. gombakensis sp. nov. and (2) from S. hexodon species group Scelimena marta sp. nov. Catalogue of Scelimenini genera (15) and species (100) is presented and taxonomy and biogeography of the tribe are discussed. New and resurrected combinations are: Falconius becvari (Buzzetti & Devriese, 2008) comb. nov. (of Gavialidium becvari), Gavialidium carli Hebard, 1930 comb. resurr. (of Bidentatettix carli), Indoscelimena india (Hancock, 1907) comb. nov. (of Scelimena india), Paragavialidium nodiferum (Walker, 1871) comb. nov. (of Platygavialidium nodiferum), Platygavialidium productum (Walker, 1871) comb. nov. (of Gavialidium productum), Scelimena hexodon (Haan, 1843) comb. resurr. (of Hexocera hexodon), Scelimena rosacea (Hancock, 1915) comb. resurr. (of Amphibotettix rosaceus), Tegotettix bufocrocodil (Storozhenko & Dawwrueng, 2015) comb. nov. (of Gavialidium bufocrocodil). New synonyms are: Gavialidium phangensum Mahmood, Idris & Salmah, 2007 syn. nov. (of Eufalconius pendleburyi), Gavialidium philippinum Bolívar, 1887 syn. nov. (of Platygavialidium productum comb. nov.), Hexocera Hancock, 1915 syn. nov. (of Scelimena), Paracriotettix Liang, 2002 syn. nov. (of Scelimena), Paracriotettix zhengi Liang, 2002 syn. nov. (of Scelimena melli), Scelimena mellioides Deng, 2016 syn. nov. (of Scelimena melli), Scelimena wuyishanensis Deng, 2016 syn. nov. (of Platygavialidium sinicum). The genus Scelimena is divided into six species groups. Eucriotettix neesoon Tan & Storozhenko nom. nov. is new name for homonym Eucriotettix guentheri Tan & Storozhenko, 2017. Finally, a tabular key to 15 Scelimenini genera, based on 16 morphological characters, is presented.